Spatiotemporal range dynamics and conservation optimization for endangered medicinal plants in the Himalaya - Fu-Lv Liu; Winnie Wanjiku Mambo; Jie Liu; Guang-Fu Zhu; Raees Khan; Abdullah; Shujaul Mulk Khan; Lu Lu (Global Ecology and Conservation)
Global climate change threatens the spatiotemporal distribution and resilience of species, especially those in mountainous regions. The Himalaya, a global biodiversity hotspot, harbors one of the richest medicinal plant communities, which are economically significant and contribute to human well-being through their health benefits. However, our understanding of species distribution across space and time under climate change scenarios, as well as effective conservation planning for these medicinal plants in the Himalaya, remains limited. In this study, we used the biomod2 ensemble model to predict the potential habitats of ten medicinal species using 497 occurrence points and 26 environmental variables under the past, present, and two future scenarios (2090; SSP126 and SSP585). We analyzed the spatiotemporal range dynamics of the ten species, performed their threat assessment using the redlistr R package, and developed a systematic conservation plan using Zonation 4.0 software. Our results showed that the habitat of most medicinal plants in the Himalaya have expanded their habitat range from the Last Glacial Maximum to the present, with a substantial contraction projected in both future scenarios. Six species migrated northwards towards high elevation, while four species migrated southwards. Threat assessment results indicated that all the species are endangered. Our conservation planning analysis revealed that northern parts of Pakistan such as Swat, Shangla, Hazara division, Jammu, and Kashmir are the core conservation areas for these ten species. We propose establishing additional protected areas in the Himalaya particularly in the western Himalaya for better management and conservation of endangered medicinal plants.